Shadow Theaters of the World - Chen, Fan Pen (Asian folklore studies, 2003)
This paper examines the origin of the shadow theaters of the world including those of India, Indonesia, Southeast Asia, Egypt, Turkey, China, and Europe, and the relationships among the various traditions. Theories which have been advanced are discussed and analyzed, along with suggestions of other possibilities. Although all the shadow theater traditions of the world are highly distinctive, many links and influences have existed among them. This study suggests that the shadow theater may have originated in either Central Asia or India. The Euro-Asian steppe and the seas between Africa, Asia and Southeast Asia may have served as avenues that linked disparate shadow traditions, and some influences were probably not unidirectional. The paper also refutes numerous theories concerning the relationship between Chinese Shadows and those of the rest of the world.